Molecular Evidence Suggests That Wolbachia pipientis (Rickettsiales: Anaplasmataceae) is Widely Associated With South American Sand Flies (Diptera: Psychodidae). Issue 6 (27th August 2021) - Cruz, Léo Nava Piorsky Dominici; Carvalho-Costa, Luis Fernando; Rebêlo, José Manuel Macário
Abstract: Wolbachia pipientis (Hertig) is an endosymbiotic microorganism widespread among arthropods and other invertebrate hosts, and employed in strategies to reduce the incidence of arthropod-borne diseases. Here, we used a PCR-based approach for 16S RNA and wsp genes to investigate the prevalence, geographical distribution, and strains of Wolbachia in sand flies (Diptera: Psychodidae: Phlebotominae), the main vectors of the causative agents of leishmaniasis, from three biomes in Brazil: Amazon, Cerrado, and Caatinga. We found that: 1) Wolbachia DNA is present in most (66.7%) of the sampled sand fly species, including vectors of Leishmania spp. (Ross, Trypanosomatida: Trypanosomatidae), 2) the prevalence of Wolbachia DNA varies among species and populations, 3) some strains of Wolbachia may have wider geographical and host range in South America, and 4) two phylogenetic distinct wsp sequences might represent two novel strains for Wolbachia in South America sand flies. Those findings increase the basic knowledge about Wolbachia in South American sand flies and might foster further researches on its use to reduce the transmission of sand fly-borne parasites.